2023
DOI: 10.1097/sla.0000000000005991
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Entrustable Professional Activities in General Surgery

Abstract: Objective: The ongoing complexity of general surgery training has led to increased focus on ensuring competence of graduating residents. Entrustable professional activities (EPAs) are units of professional practice that provide an assessment framework to drive competency-based education. The American Board of Surgery convened a group from the American College of Surgeons, ACGME Surgery Review Committee, and Association of Program Directors in Surgery to develop and implement EPAs in a pilot group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Summative data were collected by program CCCs at each 6-month interval and provided to the ABS; individual EPA microassessment data were kept at the program level alone. Further detail about the development of the EPA Pilot Study and initial results have been described by Brasel et al 6…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summative data were collected by program CCCs at each 6-month interval and provided to the ABS; individual EPA microassessment data were kept at the program level alone. Further detail about the development of the EPA Pilot Study and initial results have been described by Brasel et al 6…”
Section: Resultsmentioning
confidence: 99%
“…In this retrospective analysis of the ABS EPA Pilot Study conducted at 28 general surgery residency programs with assessment of 565 residents, CCC confidence in their EPA summative entrustment decisions increased with an increasing number of EPA microassessments. This study is among the first reported analyses of the ABS EPA Pilot Study and offers potentially informative data for general surgery residency programs across the US for the ongoing implementation of surgery EPAs nationally …”
Section: Discussionmentioning
confidence: 99%
“…Pilot EPAs included evaluation and management of a patient with right-lower-quadrant pain, inguinal hernia, gallbladder disease, and blunt or penetrating trauma, as well as performing general surgical consultation. As recently reported by Brasel et al, more than 6000 EPA microassessments were collected over the course of the pilot study, with 1763 summative entrustment ratings (determined by program clinical competency committees at 6-month study intervals based on accumulated microassessment data) completed for 497 residents. Increasing levels of entrustment were seen with increasing postgraduate-year level.…”
Section: Rationale For Epas In Surgerymentioning
confidence: 99%
“…Importantly, the authors noted wide variability in the numbers of microassessments completed per resident by program, with a mean (SD) of 5.6 (13.4) microassessments but a median of only 1 microassessment per resident . The pilot study allowed programs to implement EPAs and collect microassessment data using methods of their choosing, and this freedom, plus differences in program structures and cultures, likely contributed to the variability of EPA utilization during the pilot.…”
Section: Rationale For Epas In Surgerymentioning
confidence: 99%
“…[1][2][3][4][5] Despite widespread acceptance conceptually and national regulatory bodies adopting this approach to their work, fundamental challenges around implementation persist. [6][7][8][9][10] Many on-the-ground educators express uncertainty, and even scepticism, regarding scaled implementation given barriers related to educational time, structures and finances. [11][12][13] Another challenge is the lack of consistency around terminology and approach.…”
Section: Introductionmentioning
confidence: 99%